Development of a geometric surface area monitor (GSAM) for aerosol nanoparticles. (December 2017) - Cao, Leo N.Y.; Chen, Sheng-Chieh; Fissan, Heinz; Asbach, Christof; Pui, David Y.H.
Abstract: Although geometric surface area (GSA) of nanoparticles has received much attention in many fields (drug delivery, catalysts, inhalation exposure, toxicity, etc.), no appropriate instruments and methods for online measurements of GSA are readily available. Therefore, this study intends to develop a Geometric Surface Area Monitor (GSAM) to measure the GSA of spherical as well as model agglomerate/aggregate nanoparticles in nearly real-time. The GSAM consists of several existing techniques in series, including inertial impaction, unipolar charging, electrostatic precipitation, and electrical current measurement. The GSAM was first evaluated and calibrated by measuring the GSA of monodisperse nanoparticles. Spherical, aggregate, and agglomerate nanoparticles were tested in the calibration. It was found that the measured electrical current was proportional to the surface area concentration. The calibration curves obtained from the measurements of monodisperse particles was then applied for polydisperse spherical particles and compared the measured GSA with that determined by the well-known scanning mobility particle sizer (SMPS) where the GSAM had less than 10% of deviation compared with SMPS. Highlights: The Geometric Surface Area Monitor (GSAM) can measure the geometric surface area (GSA) of nanoparticles in nearly real-time. The GSAM consists of inertial impaction, unipolar charging, electrostatic precipitation, and current measurement. The instrument can measure the GSA of spherical as well as model agglomerate polydisperse nanoparticles. The GSA results here had less than 10% of deviation compared with well-known scanning mobility particle sizer.